The Influence Of Group Conformity, Consumer Attitude And Lifestyle On The Purchase Decision Counterfeit Fashion Products - Zunan Setiawan; Heny Herawati; Ratnawita Ratnawita; Syamsu Rijal; Ratih Pratiwi (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study was conducted to determine the effect of attitude, lifestyle and group conformity to the decision buying fashion products imitation. The hypothesis in this study is whether there is a significant influence of the dimensions of attitude (cognitif, affective, conative), dimensions of lifestyle (activity, interest, opini) and dimensions of group conformity (normative influence and informational influence) to the decision buying fashion products imitation. The population in this study were 887 men and women with classification age (18-25) years old and 350 samples were taken using a non-probability sampling techniques called convenience sampling. To measure, researchers adapted from Tricomponent Attitude Model Scale, AIO methods, and Peer Conformity Inventory (PCI). CFA (Confirmatory Factor Analysis) is used to test the validity of measuring instruments and Logistic Regression Analysis was used to test the research hypoteses. All testing technique performed using SPSS software 16.0 and LISREL 8.70. The result showed that there was a significant effect of attitude, lifestyle and group conformity on purchase decisions fashion products imitation. Minor hypothesis test results showed that the interest and informational influencem have a significant influence on the decision to buy fashion products imitation. Meanwhile, cognitif, affective, conative, activity, opini and normative influence didn’t have a significant influence on the decision buying fashion products imitation. The results also showed the proportion of the variance of the decision of buying a fashion products imitation described by all the independent variables was 18.7%, while 81.3% is influenced by other variables outside of this research. Researcher hope implication of this research will be more examined by adding some independent variabel. Example, demografic factors.